Investigation of the tool-tip vibration and its influence upon surface generation in flycutting. (August 2014) - Liang, Yingchun; Chen, Wanqun; An, Chenhui; Luo, Xichun; Chen, Guoda; Zhang, Qiang
Flycutting is a major machining process for flat-surface machining, which is a typical intermittent-machining process. This paper is dedicated to study the influence of the intermittent-machining force on the workpiece surface generation. In the present study, some defects are identified on the machined surface and found to be corresponded to the tool-tip vibration by the dynamic analysis and the surface-generation simulation. A theoretical model is proposed to capture the dominant factor based on the characteristic. It reveals that the defects are attributed to the changing period of the intermittent-machining force and the dynamic performance of the machine tool. Hence, a surface-generation model is proposed to take account of the tool-tip vibration and the changing of the cutting locus. The simulation results have been found to agree well with the experimental results.